Professional stigma towards clients with methamphetamine use disorder - a qualitative study - Ali Makki; Carolyn Day; Betty B. Chaar (Taylor & Francis Group, 2024)
ABSTRACTBackground: Methamphetamine use disorder (MUD) is associated with poor health outcomes. Pharmacists play a role in delivery of substance use treatment, with several studies having examined their attitudes to people with opioid use disorder, but little is known about their attitude towards people with MUD. This study aimed to explore pharmacists' perspectives on the provision of services to clients with MUD.Methods: A convenience sampling strategy was used to recruit community pharmacists across Sydney, Australia. Semi structured interviews examined views and ideas of pharmacists surrounding the treatment and management of MUD, followed by coding of transcribed interview data by all members of the research team.Results: Nineteen pharmacists completed the interviews. The main theme identified was stigma held by healthcare professionals. The almost unanimous perception amongst pharmacists was fear and apprehension towards people with MUD, including underlying assumptions of criminality, misinformation regarding people with MUD, and lack of education and knowledge surrounding MUD.Conclusion: A substantial amount of stigma towards people with MUD was found in this study. Negative attitudes by healthcare professionals can perpetuate healthcare disparities and impede the accessibility of future treatment programs for people with MUD. Appropriate educational interventions on MUD for pharmacists are needed.